Pengaruh Pembelajaran Kontekstual Terhadap Pemahaman Konsep Dimensi Tiga Peserta Didik Kelas XII SMA Negeri 2 Baubau - Suwarni La Usa (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2021)
The purpose of this study was to determine the effect of contextual learning on the understanding of three dimensional concepts in XII grade students of SMA Negeri 2 Baubau. This type of study was quantitative research. The population in this study were all students of class XII SMA Negeri 2 Baubau which consisted of 11 classes, namely 396 students. The instruments used were tests and questionnaires. Data collection in this study was carried outu using a test consisting of 10 items in the form of an essay for the final test. Samples were taken using a random sampling technique, namely class XII IPA 8 as an experimental class as many as 36 students and class XI IPA II as a control class as many as 36 students at SMA Negeri 2 Baubau. Data collection techniques in research using tests and questionnaires. The technique of collecting data in the study used a questionnaire. The analysis technique used by the researcher was also 2 types of statistical analysis, namely descriptive statistics and inferential statistics. Before testing the hypothesis, a prerequisite test will be carried out, such as the normality test and the homogeneity test. Based on the results of calculations using the independent samples t-test, the t value was 3.593. For the t-table value at the significance level of 0.05 (5%) and db = 70, which was 2,000. Based on this value t-count t-table, the study hypothesis was accepted. So that, it could be concluded that contextual learning had significant influence on understanding the three dimensional concept of XII grade at SMA Negeri 2 Baubau.